Adaptive region tracking control with prescribed transient performance for autonomous underwater vehicle with thruster fault. (15th January 2020) - Liu, Xing; Zhang, Mingjun; Wang, Suming
Abstract: This paper investigates the problem of region tracking control with prescribed transient performance for autonomous underwater vehicles (AUVs) in presence of ocean current and thruster fault. An adaptive region tracking control scheme with prescribed transient performance is proposed. On the basis of prescribed performance control concept, the proposed control scheme transforms the tracking error into a virtual error by combining with a prescribed performance function. And then the control law is derived by constructing a type piecewise and smooth Lyapunov function in the framework of backstepping technique. Moreover, the compensation of ocean current, modelling uncertainty and thruster fault is achieved by estimating the bound of the general uncertainty term and the variation of the thruster distribution matrixes. Finally, the proposed region tracking control scheme is applied on ODIN AUV, and the simulation results verify the effectiveness of the proposed method. Highlights: A region tracking FTC scheme with prescribed transient performance is proposed. Ocean current and thruster fault is compensated by on-line adaptive technique. The proposed region tracking control scheme is verified by simulation results.